Effects of some pesticides on in vitro Male gametophyte performance of almond (Prunusamygdalus batsch) and plum (Prunus domestica L.) - Topdemir, Aykut (Parlar Scientific Publications, 2019)
The aim of this study is to investigate the effects of pesticides on in-vitro pollen germination and pollen tube growth of almond (Prunus amygdalus Batsch) and plum (Prunus domestica L.) plants. Prunus amygdalus Batsch and Prunus domestica L. flowers were exposed to 5 different solutions of four different pesticide active substances (carbendazim, thiram, cyprodinil and dodine), each of which was diluted with distilled water (1/2 to 1/32). A Brewbaker-Kwack medium was used for pollen germination. Pollen germination rate and pollen tube growth of pollens decreased with exposure to active ingredients of pesticides. The pollen germination rate of almond (Prunus amygdalus Batsch) plant was most and least affected by thiram and dodine, respectively, while that of plum (Prunus domestica L.) plant was most and least affected by cyprodinil and thiram, respectively. Pollen tube lengths show that the pollens of almond (Prunus amygdalus Batsch) plant was most and least affected by carbendazim and cyprodinil, respectively. while those of plum (Prunus domestica L.) plant was most and least affected by carbendazim and dodine, respectively. © 2019 Parlar Scientific Publications. All rights reserved.
Keywords: Pesticides; Pollen germination; Pollen tube growth; Prunus amygdalus Batsch; Prunus domestica L